Constitutive activation of alternative nuclear factor kappa B pathway in canine diffuse large B-cell lymphoma contributes to tumor cell survival and is a target of new adjuvant therapies. Issue 7 (3rd July 2017) - Seelig, Davis M.; Ito, Daisuke; Forster, Colleen L.; Yoon, Una A.; Breen, Matthew; Burns, Linda J.; Bachanova, Veronika; Lindblad-Toh, Kerstin; O'Brien, Timothy D.; Schmechel, Stephen C.; Rizzardi, Anthony E.; Modiano, Jaime F.; et al.
Abstract: Activation of the classical nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) pathway is a common molecular event observed in both human and canine diffuse large B-cell lymphoma (DLBCL). Although the oncogenic potential of the alternative NFκB pathway (ANFκBP) has also been recently identified in DLBCL, its precise role in tumor pathogenesis and potential as a treatment target is understudied. We hypothesized that up-regulation of the ANFκBP plays an important role in the proliferation and survival of canine DLBCL cells, and we demonstrate that the ANFκBP is constitutively active in primary canine DLBCL samples and a cell line (CLBL1). We further demonstrate that a small interfering RNA inhibits the activation of the NFκB pathway and induces apoptosis in canine DLBCL cells. In conclusion, the ANFκBP facilitates survival of canine DLBCL cells, and thus, dogs with spontaneous DLBCL can provide a useful large animal model to study therapies targeting the ANFκBP.